TANTANGAN PENERAPAN REKAM MEDIS ELEKTRONIK (RME) UNIT RAWAT JALAN (RJ) RSU AZ-ZAHRA - Permatasari, Dian; Ipnuwati, Sri (ZONAsi: Jurnal Sistem Informasi, 2025)
The use of information technology in the healthcare sector is rapidly advancing, particularly through the implementation of Electronic Medical Records (EMR), which aims to improve the efficiency, accuracy, and accessibility of patient data. However, the adoption of EMR in hospitals, especially in outpatient units, often encounters various challenges. This study aims to identify and analyze the key challenges in implementing EMR in the outpatient unit of RSU Aazzahra. A descriptive qualitative approach was used, with data collected through direct observation, interviews with healthcare personnel, and document analysis. The findings indicate that the main challenges include limited IT infrastructure, lack of staff competence in operating the system, resistance to change from manual to digital systems, and suboptimal system integration between service units. This study provides a realistic overview of the obstacles in implementing health information systems and offers valuable insights for the development of more effective and sustainable solutions in hospital information systems.